Dietary factors related to body weight in adult Vietnamese in the rural area of Haiphong, Vietnam: the Korean Genome and Epidemiology Study (KoGES) - Kim, Sun Hye (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2010)
The objectives of this study were to examine the association between dietary factors and underweight and overweight adult Vietnamese living in the rural areas of Vietnam. A cross-sectional study of 497 Vietnamese aged 19 to 60 years (204 males, 293 females) was conducted in rural areas of Haiphong, Vietnam. The subjects were classified as underweight, normal weight, and overweight based on BMI. General characteristics, anthropometric parameters, blood profiles, and eating habits were obtained and dietary intake was assessed using 24-hour recalls for 2 consecutive days. A high prevalence of both underweight (BMI < 18.5 kg/m(2)) and overweight (BMI ≥ 23 kg/m(2)) individuals was observed (14.2% and 21.6% for males and 18.9% and 20.6% for females, respectively). For both genders, the overweight group were older than the under- and normal weight groups (P = 0.0118 for males and P = 0.0002 for females). In female subjects, the overweight group consumed significantly less cereals (P = 0.0033), energy (P = 0.0046), protein (P = 0.0222), and carbohydrate (P = 0.0017) and more fruits (P = 0.0026) than the underweight group; however, no such differences existed in males. The overweight subjects overate more frequently (P = 0.0295) and consumed fish (P = 0.0096) and fruits (P = 0.0083) more often. The prevalence of both underweight and overweight individuals pose serious public health problems in the rural areas of Vietnamese and the overweight group was related to overeating and high fish and fruit consumption. These findings may provide basic data for policymakers and dieticians in order to develop future nutrition and health programs for rural populations in Vietnam.